Dynamic alterations and clinical implications of the plasma proteome in pediatric sepsis - Shiyuan Fan; Xinglv Liu; Zichi Zhao; Yanjuan Liu; Yu Jiang; Saizhen Zeng (European Journal of Medical Research)
Abstract Background Current sepsis biomarkers have limitations, but mass spectrometry-based proteomics can identify patients at high risk of mortality or organ dysfunction, identify the molecular mechanisms of pediatric sepsis, and reveal personalized biomarkers and therapeutic strategies, with high-risk cohorts benefiting from early and accurate identification through clinical biomarkers. Methods The young mice were randomly divided into sepsis and sham groups(D0), and then the plasma was dissected at D0, Day 1(D1), Day 3(D3), and Day 7(D7) after surgery for additional protein identification by liquid chromatography-mass spectrometry (LC/MS) proteomics. Subsequently, data from 66 cases of children diagnosed with sepsis upon admission to Pediatric Intensive Care Unit at Hunan Provincial People's Hospital and The First Affiliated Hospital of Hunan Normal University were gathered. Dynamic plasma samples (D1, D3, D7) were obtained for ELISA verification and correlation analysis of the candidate biomarkers to determine the clinical significance of sepsis candidate plasma biomarkers. Results Among the 6578 proteins identified, the septic mice groups (D1, D3, D7) demonstrated 161 differently upregulated plasma proteins. The main enriched pathways in the KEGG study were related to complement and coagulation cascades, focal adhesion, and phagosomes. ELISA test results indicated that among pediatric patients, the five candidate biomarkers (AT III, CFD, Col1α1, EGFR, Thbs1) all showed varying degrees of decrease in diagnosing sepsis. Correlation study results suggested that AT III was adversely linked with IgA, IgG, IgM, C3, with Pearson's coefficients of −0.543, −0.217, −0.526, −0.128, respectively. CFD was positively connected with IgA, IgG, IgM, and negatively correlated with C3. Col1α1, CFD, EGFR, and Thbs1 demonstrated negative correlation with suppressive CD8 + cells, while Col1α1, EGFR, and Thbs1 showed positive correlation with B cells (CD19 +). Furthermore, Col1α1, CFD, EGFR, and Thbs1 revealed positive connection with CD4 + /CD8 + . Additionally, AT III demonstrated positive connection with PT, APTT, INR, D-Dimer, and Fbg. Conversely, Col1α1 and EGFR showed negative association with PT, APTT, INR, D-Dimer, and Fbg. CFD was positively correlated with Fbg, and Thbs1 showed positive correlation with D-Dimer. Conclusion Within 1 week of sepsis onset, 161 proteins revealed alterations in young mice, with the complement and coagulation cascades, focal adhesion, and phagosome pathways showing the most significant correlations. All prospective markers reduced following the recognition of sepsis and were associated with coagulation and immunological function in pediatric patients.